Measuring the effects of co-location on emotion perception in shared virtual environments: An ecological perspective - Bente, Gary; Schmälzle, Ralf; Jahn, Nolan T.; Schaaf, Andrea (Frontiers in Virtual Reality, 2023)
Inferring emotions from others’ nonverbal behavior is a pervasive and fundamental task in social interactions. Typically, real-life encounters imply the co-presence of interactants. i.e., their embodiment within a shared space in which the trajectories of the interaction partners’ expressive body movement (EBM) create mutual social affordances. While Virtual Reality (VR) technologies and avatars are increasingly used to study emotion perception with high ecological validity and under strict experimental control it remains unclear in how far display modalities supporting the experience of co-presence in a shared virtual environment (SVE) have an impact on observers’ responses to avatars’ EBM. Drawing upon ecological approaches to emotion perception, we reasoned that sharing the space with an avatar should amplify affordances as compared to a screen display and consequently alter observers’ perceptions in terms of judgment certainty, hit rates, perceived expressive qualities (arousal and valence) and approachability. In a between-subject design, we compared the perception of 54 ten-second animations of avatars performing three daily activities (painting, sweeping, sanding) in three motional states (angry, happy, sad) either displayed in 3D as a co-present actor moving in the SVE or in 2D on a screen object placed within the SVE. Results confirm the effective experimental control of the variable of interest, showing that only perceived co-presence was significantly affected by the display modality, while perceived realism and immersion showed no difference. Results also suggest that the display modality selectively affected the perception of the three different emotions. Only for the happy stimuli the 3D display resulted in better recognition rates. Importantly though, overall hit rates were low, around and even below the chance level, while inter-observer judgements were highly correlated, indicating a consistent judgment errors across observers and stimuli. Results are discussed with regard to implications for theory method development and as well as and practical implications for future communication technology development.